Left Bundle Branch Area Pacing vs. Biventricular Pacing for Cardiac Resynchronization Therapy: A Meta-Analysis - Liu, Jiyi; Sun, Fengzhi; Wang, Zefeng; Sun, Jiao; Jiang, Xue; Zhao, Weilong; Zhang, Zhipeng; Liu, Lu; Zhang, Shulong (Frontiers in Cardiovascular Medicine, 2021)
Abstract Background: Left bundle branch area pacing (LBBAP) is a recently proposed method for conduction system pacing. We performed a meta-analysis of controlled studies to compare the clinical outcome in patients who received LBBAP versus biventricular pacing (BVP) for cardiac resynchronization therapy (CRT). Methods: PubMed, Embase and Cochrane’s Library databases were searched for relevant controlled studies. A random-effect model incorporating the potential heterogeneity was used to synthesize the results. Results: Four non-randomized controlled studies including 249 patients with heart failure for CRT were included, and the patients were followed for 6-12 months. Compared to BVP, LBBAP was associated with significantly shortened QRS duration (mean difference [MD]: -29.18ms, 95% confidence interval [CI]: -33.55 to 24.80, I2 = 0%, P<0.001), improved left ventricular ejection fraction (MD: 6.93%, 95% CI: 4.69 to 9.17, I2 = 0%, P<0.001), reduced left ventricular end-diastolic dimension (MD: -2.96mm, 95% CI: -5.48 to -0.44, I2 = 0%, P=0.02), and improved New York Heart Association class (MD: -0.54, 95% CI: -0.84 to -0.24, I2 = 65%, P<0.001). Moreover, patients who received LBBAP were more likely to achieve echocardiographic (odds ratio [OR]: 5.04, 95% CI: 2.17 to 11.69, I2 = 0%, P<0.001) and clinical (OR: 7.33, 95% CI: 1.62 to 33.16, I2 = 0%, P=0.01) CRT response. Conclusion: Current evidence from non-randomized studies suggests that LBBAP appears to be a promising method for CRT, which is associated with more remarkable improvements of symptoms and cardiac function in heart failure patients with indication for CRT.